2010
DOI: 10.3109/17435390.2010.516844
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of cellular toxicity of TiO2nanoparticles for cardiac tissue engineering applications

Abstract: Because of the increased use of titanium dioxide (TiO2) nanoparticles (NPs) in tissue engineering (TE), and in new constructs for cardiac TE, their effect was studied on three relevant cell types: Adult rat ventricular cardiomyocytes, human embryonic stem cell-derived cardiomyocytes (hESC-CM) and fibroblasts. For adult rat myocytes, 10 μg/mL TiO2 NPs showed no significant effect on myocyte survival over 24 h or acute myocyte contractility. Increasing the concentration to 100 μg/mL was seen to reduce contractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 27 publications
1
27
2
1
Order By: Relevance
“…They have shown a dose effect on proliferation and cell death. Recently, survival and contractility of adult rat ventricular CM and human embryonic stem cell-derived CM were evaluated after incubation with TiO 2 nanoparticles (TiONts spherical counterparts) (Jawad et al 2011). A 10 mg.mL À1 dose (maximal dose used in the present study) did not show significant effect on myocyte survival and contractility over 24 h, but it was shown to reduce the beating rate of the stem cell-derived CM by 24 h.…”
Section: Introductionmentioning
confidence: 76%
“…They have shown a dose effect on proliferation and cell death. Recently, survival and contractility of adult rat ventricular CM and human embryonic stem cell-derived CM were evaluated after incubation with TiO 2 nanoparticles (TiONts spherical counterparts) (Jawad et al 2011). A 10 mg.mL À1 dose (maximal dose used in the present study) did not show significant effect on myocyte survival and contractility over 24 h, but it was shown to reduce the beating rate of the stem cell-derived CM by 24 h.…”
Section: Introductionmentioning
confidence: 76%
“…For myocytes, 100 μg/mL of NPs decreased the contraction amplitude over 24 h; the beating rate of hESC‐CMs was reduced significantly after exposure to NPs (10 μg/mL) for 24 h. For the fibroblasts, 5–150 μg/mL of the TiO 2 NPs reduced cell proliferation and obviously increased cell death after 4 days of exposure. These data suggested that the NPs had potential negative effects if they were used in rapidly degrading polymers for MTE applications . LDH is widely expressed in the heart, liver, and other tissues, and plays an important role in glycolysis and glyconeogenesis.…”
Section: Bio‐toxicitymentioning
confidence: 98%
“…CeO 2 also inhibit CSE‐induced phosphorylation of I κ B α , the inhibitory subunit of NF‐ κ B. Another study demonstrated that TiO 2 NP had only minimal impacts on adult cardiac myocyte function, but showed higher toxicity in embryonic stem cell derived cardiac myocytes 58. Collectively, these results demonstrate that NP such as CeO 2 may have different oxidative capacities depending on the exposed cell type and TiO 2 NP may have greater cardiac cytotoxicity in heart patients that have undergone stem cell grafts.…”
Section: Cardiac Outcomesmentioning
confidence: 99%